E-Commerce Security Issues, Then and Now: Thoughts Stimulated by an Historic Paper by Dez Blanchfield (2000) on E-Commerce Security - Shepherd, Graham (Journal of Telecommunications and the Digital Economy, 2024)
Simon Moorhead’s recent historical reprint (December 2024) revisiting Dez Blanchfield’s December 2000 paper in TJA on e-commerce security has stimulated this author to make additional comments on the weaknesses of major websites and of email systems today in permitting fraud and deception, in comparison to 24 years ago.